Evidence based tobacco use prevention among youth - Kilibarda, Biljana; Vukovic, Dejana (Medicinski podmladak, 2020)
Evidence based tobacco use prevention among youth For majority of smokers, onset of smoking occurs during adolescence, period of intensive growth and development, and this early smoking initiation is associated with many adverse health effects. Due to the chronic and recurrent nature of nicotine dependence that can manifest soon after onset, smoking prevention measures include not only prevention of onset, but also prevention of transition from experimentation to chronic tobacco use and dependence and smoking cessation. Effective preventive measures should be based on relevant theory and scientific evidence on behavior determinants. Findings from research conducted in previous decades show that some preventive measures can be ineffective, while other are still under debate. In this review article we present evidence from researches on effectiveness of school programs, community based programs, media campaigns and stress the importance of considering new challenges in tobacco control and other promising strategies as well as need for early detection of nicotine dependence signs among adolescents. In practice, many preventive measures are not based on theory and some interventions can be contra productive. Regardless of type of intervention and setting in which is implemented, it is of importance to take into account context for its implementation.